2017
DOI: 10.1016/j.ijmecsci.2017.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Surface effect on the resonant frequency of Timoshenko nanobeams

Abstract: The dynamic behavior of a Timoshenko nanobeam would be significantly different from a macro-one due to the large ratio of surface area to volume of nanomaterials. Furthermore, the shear deformation effect would be obvious for a Timoshenko nanobeam in contrast to an Eulerian one. In this paper, a recently developed elastic theory is adopted in order to predict the resonant frequency of a Timoshenko nanobeam, in which not only the surface effect but also the shear deformation effect and the rotary inertia one ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Jia et al. 41 studied SE on the resonant frequency of Timoshenko nanobeams. They concluded that with considering the effect of SE, the resonant frequency of a fixed–fixed Timoshenko nanobeam would be improved, while that of a cantilevered one would be weakened by the SE in contrast to the corresponding classical solutions.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Jia et al. 41 studied SE on the resonant frequency of Timoshenko nanobeams. They concluded that with considering the effect of SE, the resonant frequency of a fixed–fixed Timoshenko nanobeam would be improved, while that of a cantilevered one would be weakened by the SE in contrast to the corresponding classical solutions.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…In addition, the role of surface effect on the resonant behavior of Timoshenko nanobeams with the different boundary conditions was studied. [133,135] For instance, surface effect in a doubly clamped nanobeam would improve the resonant frequency, while for a nanocantilever, the resonant frequency would be weakened by the surface effect. [135] Recently, an in-depth review on size-dependent mechanical properties of nanowires was published.…”
Section: Continuum Mechanical Systemsmentioning
confidence: 99%
“…[133,135] For instance, surface effect in a doubly clamped nanobeam would improve the resonant frequency, while for a nanocantilever, the resonant frequency would be weakened by the surface effect. [135] Recently, an in-depth review on size-dependent mechanical properties of nanowires was published. [139]…”
Section: Continuum Mechanical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both parameters are easily found from material handbooks or simple molecular dynamics simulations. Some statics and dynamics of beams have been well analyzed by surface energy density theory [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%